Online Learning Quality mediated by Self-efficacy - Retno Sari Murtiningsih (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This research aims to determine the influence of Learning Motivation, Cognitive, and Learning Interest on Online Learning Quality which is mediated by Self-Efficacy. This research uses primary data from a questionnaire totaling 87 students as respondents. The Likert scale is used to measure all variables, and data processing uses SEM-PLS. The research results show that Learning Motivation directly has a positive effect on Online Learning Quality, but when mediated by Self-efficacy it does not affect Online Learning Quality. Learning Motivation also has no positive effect on Self-efficacy. Cognitive, either directly or indirectly, mediated by Self-efficacy, does not affect Online Learning Quality, but Cognitive has a positive effect on Self-efficacy. Learning Interest has a positive effect on Self-efficacy and Online Learning Quality, but it does not affect Online Learning Quality when mediated by Self-efficacy. This research emphasizes the mediating role of Self-efficacy in the influence of Motivation, Cognitive, and Learning interest on Online Learning Quality.